ANALYSIS OF SOCIAL ATTITUDE OF STUDENTS IN CLASS 4 OF KADUAGUNG PUBLIC SCHOOL FOR THE ACADEMIC YEAR OF 2022/2023 - Tamlik, Rahma Amellia (Journal Of Educational Experts (JEE), 2023)
This study aims to describe the social attitudes of grade 4 students at SDN Kaduagung. The subjects of this study were 4th grade students at Kaduagung State Elementary School, with a total of 34 students. The data collection method used is descriptive qualitative analysis. The data collection technique was through a questionnaire instrument filled out by students, observations made by researchers and interviews with the homeroom teacher of class 4 of Kaduagung State Elementary School. The technique of checking the validity of the data is carried out using a data triangulation model. Each student has different social attitudes. The social attitude of grade 4 students at Kaduagung State Elementary School is reflected when carrying out an activity or activities at school, namely being honest, disciplined, responsible, polite, caring and confident. The social attitudes of grade 4 students at Kaduagung State Elementary School are in the very good, good, sufficient and poor categories. There are two types of social attitudes, namely positive social attitudes and negative social attitudes. The social attitude of grade 4 students at Kaduagung State Elementary School is influenced by internal and external factors. Parents and teachers are also a supporting factor in the formation of students' social attitudes.